Conservative Treatment Protocol for Keratocystic Odontogenic Tumour: a Follow-up Study of 3 Cases - Gülsün Yildirim; Hanife Ataoglu; Abdullah Kalayci; Birkan Taha Özkan; Korhan Kucuk; Alparslan Esen (eJournal of Oral Maxillofacial Research, 2010)
Background: The keratocystic odontogenic tumour is classified as a developmental cyst derived from the enamel organ or from the dental lamina. The treatment of keratocystic odontogenic tumour of the jaw remains controversial. The aim of this study was to report the outcome of our conservative treatment protocol for keratocystic odontogenic tumour.Methods: Three patients with different complaints referred to Oral and Maxillofacial Surgery Clinic, Faculty of Dentistry, Selçuk University. Initial biopsy was carried out in all patients and keratocystic odontogenic tumours was diagnosed subsequent to histopathological examination. The patients with keratocystic odontogenic tumours were treated by enucleation followed by open packing. This conservative treatment protocol was selected because of existing young aged patients. The average follow-up duration of the cases was 2 years.Results: Out of 3 cases, 2 lesions were present in mandible and 1 lesion in maxilla. There was no evidence of recurrence during follow-up. All the cases were monitored continuously with panoramic radiographs, computed tomography and clinical evaluations.Conclusions: This conservative treatment protocol for keratocystic odontogenic tumours, based on enucleation followed by open packing would be a possible choice with a view of offering low recurrence rate and low morbidity rate particularly in young patients.